Microbial infection pattern, pathogenic features and resistance mechanism of carbapenem-resistant Gram negative bacilli during long-term hospitalization. (April 2018) - Wen, Shuxian; Feng, Donghua; Lu, Zerong; Liu, Junyan; Peters, Brian M.; Tang, Hailing; Su, Danhong; Lin, Yong-Ping; Yang, Ling; Xu, Zhenbo; Shirtliff, Mark E.; Chen, Dingqiang
Abstract: Background: Carbapenem-resistant Gram-negative bacilli (GNB) have become an important cause of nosocomial infections of hospitalized patients. Methods: To investigate the microbial infection patterns and molecular epidemiology characteristics of the carbapenem-resistant GNB isolates from a long-term hospitalized patient, antimicrobial susceptibility testing, phenotypic screening test for carbapenemase production, PCR screening and DNA sequencing of carbapenemase genes, repetitive extragenic palindromic sequence-based PCR (REP-PCR), multilocus sequencing typing (MLST) and genetic environment analysis were performed. Results: Twelve strains with carbapenemase genes were detected from 63 carbapenem-resistant isolates, including two bla IMP-25 -carrying Pseudomonas aeruginosa, one bla NDM-1 -carrying Citrobacter freundii, three bla NDM-1 -carrying Klebsiella pneumoniae and six bla KPC-2 -carrying K. pneumoniae . Only the bla NDM-1 genes were successfully transferred from three K. pneumoniae strains to Escherichia coli C600 by conjugation. Genetic environment of bla IMP-25, bla NDM-1 and bla KPC-2 genes in our study were consistent with previous reports. Molecular typing of K. pneumoniae performed by MLST revealed that most of the isolates belonged to ST11. bla NDM-1 -carrying K. pneumoniae sequencing type 1416 was first reported in our study. Conclusions: Carbapenem-resistant GNB are common pathogens during long-term hospitalization, and ST11 bla KPC-2 -carrying K. pneumoniae is the dominant bacterium in our study. Colonization and horizontal transmission of resistance by plasmids of carbapenem-resistant GNB have increased the risks of persistent infection and mortality of long-term hospitalized patients. Highlights: bla NDM-1 -positive Klebsiella pneumoniae ST1416 was first reported in China. Gram-nagative bacilli is dominated in infection during long-term hospitalization. Carbapenemase genes were associated with different genetic elements in different bacterial strains.